Literasi Matematika dalam Pengembangan LKM Berbasis HOTS Menggunakan Model PBL Melalui Daring - Anita Hutagaol (Universitas Asahan, 2020)
AbstractThis research is a research development that aims to obtain validity, practicality, and effectiveness of Student Worksheets based on HOTS through online during on flat material and space, as an effort to describe students' mathematical literacy abilities. The development model used was the 4D model (Define, Design, Develop, and Disseminate). The research method, namely the descriptive method and design used during the implementation of Student Worksheets based on HOTS, refers to the stage of Classroom Action Research (CAR). The results of the Student Worksheets based on HOTS research that was developed show that: 1) validity is in very good criteria with an average score of 3.52 obtained from media and material experts; 2) practicality, obtained based on the results of interviews stating that the Student Worksheets based on HOTS is easy to use and the language is easy to understand; and 3) effectiveness, obtained through the ability of lecturers to manage to learn quite well with an average score of 3.6. Achieving the ideal percentage of time for student activities to meet the tolerance criteria of 5%. Student responses conducted through questionnaires after learning were very positive with an average score of 93.86. Student mathematics literacy ability test shows that 71.15% with medium criteria after participating in learning using the Student Worksheets based on HOTS developed. So it can be concluded that Student Worksheets based on HOTS using PBL models online have met the criteria for developing learning tools that are valid, practical and effective and are appropriateKeywords: During, Mathematical Literacy, Problem Based Learning, Student Worksheets based on HOTS AbstrakPenelitian ini merupakan penelitian pengembangan yang bertujuan untuk memperoleh kevalidan, kepraktisan, dan keefektipan LKM Berbasis HOTS melalui daring pada materi bangun datar dan ruang, sebagai upaya mendeskripsikan kemampuan literasi matematika mahasiswa. Model pengembangan yang digunakan adalah model 4D (Difine, Design, Develop, and Disseminate). Adapun metode penelitian yakni metode deskriptif dan rancangan yang digunakan pada saat implementasi LKM berbasis HOTS mengacu kepada tahapan Penelitian Tindakan Kelas (PTK). Hasil penelitian LKM berbasis HOTS yang dikembangkan menunjukkan bahwa: 1) kevalidan berada pada kriteria sangat baik dengan rata-rata skor 3,52 yang diperoleh dari ahli media dan materi; 2) kepraktisan, diperoleh berdasarkan hasil wawancara menyatakan bahwa LKM berbasis HOTS mudah digunakan dan bahasanya mudah dimengerti; dan 3) keefektivan, diperoleh melalui kemampuan dosen mengelola pembelajaran cukup baik dengan rata-rata skor 3,6. Pencapaian persentase waktu ideal aktivitas mahasiswa memenuhi kriteria toleransi 5%. Respon mahasiswa yang dilakukan melalui pengisian angket setelah pembelajaran sangat positif dengan rata-rata skor 93,86. Tes kemampuan literasi matematika mahasiswa menunjukkan bahwa 71,15% dengan kriteria sedang setelah mengikuti pembelajaran menggunakan LKM berbasis HOTS yang dikembangkan. Sehingga diperoleh kesimpulan bahwa LKM berbasis HOTS menggunakan model PBL melalui daring telah memenuhi kriteria pengembangan perangkat pembelajaran yaitu valid, praktis dan efektif serta layak digunakan.Kata kunci: Daring, Literasi Matematika, LKM Berbasis HOTS, Problem Based Learning